Reinventing Employee Onboarding - Staats, Bradley; Gino, Francesca; Cable, Daniel (MIT Sloan Management Review, 2013)
The first day on the job at a new organization is commonly structured around introducing employees to the work environment and company culture. The authors found that the traditional methods of onboarding have some serious weaknesses. Subordinating one's identity and unique perspectives may not be optimal in the long run for either the organization or the individual employee. Socialization practices that get newcomers to behave inauthentically might not be sustainable and do not address broader issues concerning emotional exhaustion and work dissatisfaction. In studying how organizations onboard new employees, the authors developed a different approach, which they refer to as "personal-identity socialization," that had positive long-lasting effects for both companies and employees. It involves encouraging newcomers to express their unique perspectives and strengths on the job and inviting them to frame their work as a platform for doing what they do best. In field research at Wipro BPO, a business process outsourcing firm in Bangalore, India, the authors found that the company was experiencing high turnover rates that were comparable to those of the industry (50% to 70% annually). Its onboarding process was tightly organized around transferring the company culture to new employees, as is typical in many other organizations. In Wipro's traditional program, new employees (known as "agents") underwent training in 15- to 25-person teams. During the first days of orientation, they learned about the company and received human resources information. The authors studied whether an alternative approach to onboarding made a difference in performance and retention. They found that when socialization focused on individual identity, employees were more than 32% less likely to quit their jobs during the first six months at the company than those employees who received Wipro's traditional onboarding approach. Moreover, employees who went through the approach to onboarding that focused on individual identity received customer evaluations that were significantly more positive than those who went through Wipro's standard onboarding process. The authors conclude that giving newcomers the opportunity to express themselves at work bolstered employees' self-esteem and allowed them to express a positive identity during a period that employees often find stressful. By making relatively small investments in socialization practices, the authors found that companies ca...